Penguatan Pengelolaan dan Pemanfaatan Website Kelurahan Banguntapan Dalam Mendukung Digitalisasi Layanan Publik - Loli, Yanuarius Asan; Nurrahman, Agung (Fisip UIN Sunan Gunung Djati Bandung, 2025)
The digitization of public services is a critical effort to achieve ease and transparency in government functions, often facilitated through a village website. However, not all village websites are managed optimally, a challenge observed at the Banguntapan Village website. This community service activity aimed to strengthen the management and utilization of the Banguntapan Village website to support the digitization of public services. The methods used were education, mentoring, and socialization. The results show that following these interventions, there was an 85% increase in the knowledge and skills of officials in managing the website. Additionally, this activity successfully raised public awareness regarding the existence and utilization of the website. In conclusion, the community service activities successfully enhanced both officials' capabilities and public awareness. Recommendations from this activity include the need for stronger leadership support to build a digital ecosystem, a clear division of tasks for employees, and the participation of staff in regular website management training. Furthermore, content creation should be aligned with each department's duties, and clear procedures for website management should be established.